PRODUKSI BAHAN BAKAR NABATI DARI MINYAK JARAK DENGAN BANTUAN ULTRASONIK - Umar Rusli Marasabessy; Andy Suryanto; La Ifa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
The purpose/objectives/aims of this research is to determine the effect of sound waves on the manufacture of alternative biodiesel from castor oil, besides that it is also to determine the effect of reaction time and heterogeneous catalyst concentration in obtaining biodiesel products as biofuel. This research was carried out which began with the esterification reaction to reduce free patty acid levels and continued with the trans-esterification reaction with ultrasonic heating. Product quality parameters produced include: acid number, density, viscosity, water content and gas chromatography analysis,